Research on cooperative vehicle intersection control scheme without using traffic lights under the connected vehicles environment. (August 2017) - Zheng, Yi; Jin, Lisheng; Jiang, Yuying; Wang, Fangrong; Guan, Xin; Ji, Shengyuan; Xu, Jun
To improve traffic congestion of urban intersections, this article presents a cooperative vehicle intersection control scheme without using any traffic lights, based on model predictive control theory. The assumptions are that all vehicles are fully automated and that a control unit is installed at the intersection to coordinate vehicle movements. Using connected vehicles technology, vehicles approaching the intersection from all directions are globally coordinated by integrating their states all together. The trajectories of vehicles are predicted and adjusted based on collision avoidance under relevant constraints and preferences. The control scheme prevents each pair of conflicting vehicles from approaching conflicting areas at the same time and minimizes the total collision risks of all pairs of conflicting vehicles. The simulation platform was developed to quantifiably evaluate the overall performance of the scheme. Simulation results show that the proposed scheme can significantly improve the mobility, safety, and environmental aspects of the intersection compared with conventional actuated controls. In addition, we also found that better performance can be achieved when the intersection is being operated under oversaturated conditions, and the market penetration rates of equipped vehicles exceed 30%.